On the Effectiveness of Stock Index Futures for Tail Risk Protection - Zouari, Hammadi (International Journal of Economics and Financial Issues, 2022)
This paper examines the effectiveness of using stock index futures contracts as substitutes for fixed-income securities in implementing expected shortfall targeting strategy. We find that the futures-based implementation outperforms its index-and-bill counterpart both in terms of downside protection and risk-adjusted performance at daily rebalancing frequency. This outperformance is driven not only by the transaction cost advantage, but also by the replication imperfections due to futures mispricing providing over the long term a better participation in upward market movements. When less frequent rebalancing intervals are used, the futures-based implementation becomes less effective at protecting the downside risk but still capture better the upside potential of the index.